Uso de rejeitos do granito rain forest para a produção de revestimentos cerâmicos com baixa absorção de água - Cabral, Daniel Henrique Pires (2009)
Increase of building construction in Brazil has enhanced the need for the exploitation of dimensional and ornamental stones. On the other hand, this activity has caused environmental problems due to the vast amount of residues created by the extraction and processing of granites and marble stones. Recycling of such residues is seen, nowadays, as a possible solution that allies the benefits of environmental conservation to the economic advantages of reuse of sometimes scarce materials, thus contributing to the sustainable development. The present work studies the technical viability of using ‘Rain Forest’ granite rejects as an alternative raw material for the fabrication of ceramic tiles with low water absorption. Residues of the ‘Rain Forest’ granite were crushed, ground and sieved. The resulting powder was characterized by x-ray diffraction and x-ray fluorescence and thermoanalysis (TGA and DTA). Specific surface area of the powder was also determined by BET. Test samples were prepared by pressing prismatic bars from the powder. These bars were sintered in a muffle furnace, in air, at the temperatures of 1155, 1165, 1175, 1185 and 1195°C. Physical and mechanical properties were determined by several measurements, tests and technique such as: linear retraction upon firing, water absorption, apparent porosity, apparent specific gravity, modulus of rupture (3-pt bending), Knoop microhardness, and microscopy (both optical and SEM). Results obtained have shown that the residues investigated can be used as a raw material for the tile industry. Results of water absorption tests for samples sintered at the five temperatures studied are compatible with those required by the brazilian standards (NBR 13818/1997), However, after a careful analysis of all the results obtained in this research, it can be said that the test samples sintered at 1175°C presented slightly better characteristics, since they did not suffer from dimensional instabilities like the ones observed with samples sintered at 1195°C.